2022
DOI: 10.1038/s42003-022-03651-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic sequestration of p53 by lncRNA-CIRPILalleviates myocardial ischemia/reperfusion injury

Abstract: Myocardial ischemia/reperfusion (MI/R) injury is a pathological process that seriously affects the health of patients with coronary artery disease. Long non-coding RNAs (lncRNAs) represents a new class of regulators of diverse biological processes and disease conditions, the study aims to discover the pivotal lncRNA in MI/R injury. The microarray screening identifies a down-regulated heart-enriched lncRNA-CIRPIL (Cardiac ischemia reperfusion associated p53 interacting lncRNA, lncCIRPIL) from the hearts of I/R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Collectively, lncRNA-CIRPIL, lncRNA Fendrr and LINC01588 were shown to be downregulated in myocardial I/R mice or rats and to function as negative mediators of myocardial I/R-induced cardiomyocyte apoptosis by enhancing E3 ubiquitin ligases (COP1, CHIP, MDM2 and WWP2) in vivo . First, lncRNA-CIRPIL interacts with p53 and sequesters it in the cytoplasm, directly accelerating the ubiquitin-regulated degradation of p53 by upregulating the expression of E3 ubiquitin ligases COP1, CHIP and MDM2, thereby attenuating myocardial A/R-induced apoptosis and injury ( 41 ). Similar to lncRNA-CIRPIL, lncRNA Fendrr suppresses myocardial H/R-induced apoptosis by facilitating the ubiquitination degradation of p53 via COP1 ( 42 ).…”
Section: Crosstalk Between Ubiquitin Ligases and Ncrnas Drives Cardia...mentioning
confidence: 99%
See 3 more Smart Citations
“…Collectively, lncRNA-CIRPIL, lncRNA Fendrr and LINC01588 were shown to be downregulated in myocardial I/R mice or rats and to function as negative mediators of myocardial I/R-induced cardiomyocyte apoptosis by enhancing E3 ubiquitin ligases (COP1, CHIP, MDM2 and WWP2) in vivo . First, lncRNA-CIRPIL interacts with p53 and sequesters it in the cytoplasm, directly accelerating the ubiquitin-regulated degradation of p53 by upregulating the expression of E3 ubiquitin ligases COP1, CHIP and MDM2, thereby attenuating myocardial A/R-induced apoptosis and injury ( 41 ). Similar to lncRNA-CIRPIL, lncRNA Fendrr suppresses myocardial H/R-induced apoptosis by facilitating the ubiquitination degradation of p53 via COP1 ( 42 ).…”
Section: Crosstalk Between Ubiquitin Ligases and Ncrnas Drives Cardia...mentioning
confidence: 99%
“…Moreover, LNC01588 can make direct contact with the HNRNPL protein and upregulate the E3 ubiquitin ligase WWP2, which then reduces the levels of downstream SEPT4, thereby ameliorating myocardial oxidative stress and MI during myocardial I/R damage ( 43 ). On the other hand, inhibition of p53 ubiquitination degradation and inhibition of WWP2 attenuate the protective effects of lncCIRPIL and LINC01588 ( 41 , 43 ). Conversely, the ZFP36L2- lncRNA PVT1-miR-21-5p-MARCH5 axis positively affects the fission and fusion of mitochondria and cardiomyocyte apoptosis following myocardial I/R.…”
Section: Crosstalk Between Ubiquitin Ligases and Ncrnas Drives Cardia...mentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, in the cytoplasm, lncRNAs are primarily influenced by post-transcriptional events, including maintaining the stability of mRNA, sponging microRNAs to influence gene silencing, and regulating the integrity and activity of protein complexes [ 20 , 21 ]. Additionally, certain cytoplasmic lncRNAs can indirectly impact transcription by interacting with transcription factors [ 22 ]. Besides conventional regulatory mechanisms, recent studies have identified open reading frames (ORFs) within some cytoplasmic lncRNAs, suggesting they can encode functional peptides, and perform significant roles in various pathological processes [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%